Comparison between Customary Legal Systems and Modern Legal Systems in the Context of Globalization - Triasmono, Hari; Ruslie, Ahmad Sholikhin (International Journal of Law and Society, 2024)
The transformation of traditional legal systems is an essential issue in the context of globalization that affects the sustainability of conventional and modern legal systems. A comparison between these two legal systems can provide valuable insights into efforts to understand the impact of this transformation. This research aims to analyze the differences and similarities between customary legal systems and modern legal systems in the context of globalization and to understand the impact of the transformation of traditional legal systems on society and legal policy. This type of research is comparative research with a qualitative approach. Data was obtained from document studies, interviews and literature studies. Data analysis in this research was carried out using a comparative method, namely comparing data received from the customary and modern legal systems. The research results show that the transformation of traditional legal systems in the context of globalization has given rise to new dynamics between customary and contemporary legal systems. The pressure of globalization makes traditional legal systems adapt to modern legal standards, threatening the validity of customary legal systems. However, globalization also opens the door to changes in traditional legal systems, creating complexity when comparing the two legal systems.